Genetic Diversity of Enterocytozoon bieneusi in Diarrheic Shelter Dogs in Romania: First Molecular and Phylogenetic Evidence - Mirela Imre; Gheorghe Dărăbuș; Sorin Morariu; Krisztián Szabó; Marius-Stelian Ilie; Tiana Florea; Alexandra Pocinoc; Reem Awwad; Kálmán Imre (Pathogens, 2025)
Enterocytozoon bieneusi is one of the most common microsporidian parasites, primarily infecting the intestinal epithelial cells of a broad range of animal species, including humans. To date, no scientific reports have documented Enterocytozoon spp. in animal hosts in Romania. This study aimed to assess the occurrence and genetic characteristics of E. bieneusi in shelter dogs, as well as its potential public health relevance. Between December 2022 and May 2025, a total of 112 freshly voided diarrheal fecal samples were collected from dogs housed in a shelter near Timișoara Municipality, Romania. The samples were subjected to molecular analysis using a two-step nested polymerase chain reaction (PCR) targeting the internal transcribed spacer (ITS) region of the rRNA gene. The resulting sequences were deposited in GenBank® and analyzed phylogenetically. PCR analysis revealed E. bieneusi DNA in 11 (9.8%) samples, identifying two genotypes, with PtEb IX (n = 10) as the dominant genotype and BEB4 (n = 1), which has zoonotic potential. A significant difference in prevalence was found between juvenile (23.1%) and adult (5.8%) dogs (p = 0.026). Phylogenetic analysis of the ITS sequences showed that the isolates clustered into two distinct clades alongside reference sequences from the GenBank® database. This is the first report of E. bieneusi infection in animals in Romania, providing essential baseline data and highlighting the need for broader surveillance into its prevalence and genetic diversity in other potential hosts. These results reflect the prevalence and genetic diversity of E. bieneusi exclusively among symptomatic (diarrheic) dogs and should not be generalized to the broader shelter dog population.